Digital transformation of takaful through artificial intelligence: Trends in research and future directions - Azwar (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: This study aims to map research trends concerning the integration of Artificial Intelligence (AI) in the development of Islamic insurance (takaful). Methods: Employing bibliometric techniques, the study analyzes data retrieved from the Scopus database for the period 2015–2025. The research utilized a comprehensive query string focusing on keywords such as AI, blockchain, and takaful, followed by a rigorous data cleaning process to ensure metadata consistency. Quantitative analysis and thematic mapping were conducted using VOSviewer software to visualize publication trends, influential contributors, and emerging research clusters. Findings: The results indicate a significant increase in publications on AI and takaful, although overall output remains limited. The most productive contributors include Jan, Meskini, and Mohamed, while the most frequently cited work is Fintech and Islamic Finance: Digitalization, Development and Disruption (2019) by Alam, Gupta, and Zameni, with 86 citations. Lecture Notes in Networks and Systems and The Future of Islamic Finance: From Shari‘ah Law to Fintech are the leading publication outlets, whereas Stellar Consulting Group Ltd. records the highest institutional output. At the country level, Malaysia dominates the field with 12 publications, reflecting its strong research commitment. Thematic mapping highlights fintech, risk, company, contract, industry, design methodology approach, supervision, takaful company, and gap as central themes. Recent research emphasizes blockchain, financial inclusion, supervision, accuracy, and methodological design, while emerging but underexplored areas—such as the construction industry, government and state policy, permissioned blockchain, cooperation, and order—offer considerable potential for future inquiry. Conclusion: Research on AI in takaful is steadily expanding but remains in its formative stage. The field is highly interdisciplinary, with fintech and blockchain emerging as dominant themes, yet substantial opportunities remain for further exploration. Novelty/Originality of this article: This study provides the first systematic bibliometric mapping of AI in takaful, capturing publication trends, influential authors, institutions, and themes.